Medial intracranial carotid artery calcifications and hematoma expansion in deep intracerebral hemorrhage - Federico Mazzacane; Stefan Moraru; Beatrice Del Bello; Federica Ferrari; Erica Ferro; Alessandra Persico; Jawed Nawabi; Alessandro Padovani; Anna Cavallini; Andrea Morotti (Annals of Clinical and Translational Neurology)
Abstract Background Medial intracranial carotid artery calcifications (ICAC) are associated with impaired vascular physiology, increased arterial stiffness and pulse pressure. Their presence might therefore be associated with increased risk of intracerebral hemorrhage (ICH) expansion, according to the avalanche model. We explored the association between ICAC presence and pattern and hematoma expansion (HE). Methods Retrospective analysis of a monocentric, prospectively collected cohort of ICH patients admitted between June 2017 and October 2023. ICAC pattern was determined by Kockelkoren's rating scale on admission CT; medial ICAC were defined with a >6 points cutoff. A follow‐up CT scan was performed within 72 h. HE was analyzed as a dichotomous (≥6 mL and/or ≥33%) and as a categorical (none/mild/moderate/severe) variable, and its predictors were explored with logistic and ordinal regression respectively, accounting for baseline volume, onset‐to‐CT time, and anticoagulation. All the analyses were stratified by ICH location (supratentorial deep vs lobar ICH). Results A total of 201 patients were included (median age 78, 42% females, 59% deep ICH). Medial ICAC were significantly more common in deep ICH with HE compared with non‐expanders (72% vs 49%, p = 0.03), whereas there was no association between ICAC and HE in lobar ICH (53% vs 52%, p = 0.85). This association between medial ICAC and HE in deep ICH remained significant in logistic (aOR 3.11, 95% CI [1.19–9.06], p = 0.03) and ordinal regression (acOR 2.42, 95% CI [1.19–4.99], p = 0.01). Interpretation Ipsilateral medial ICAC are associated with higher odds of HE in deep ICH. Our findings are best interpreted as hypothesis generating, requiring prospective validation and further research to characterize the underlying biological mechanisms.